The Kartu Tani Program's Effect on Farmers' Satisfaction - Norbertus Citra Irawan; Suswadi; Kusriani Prasetyowati; Mahananto; Agung Prasetyo; Teguh Supriyadi (JURNAL ILMIAH AGRINECA, 2023)
This study raises the issue of farmer satisfaction as a farmer card (kartu tani) user as the main focus. The aim is to measure farmer satisfaction using the farmer card (FC). The research was conducted using the case study method with a deliberate selection of research locations in Karanganyar, Sukoharjo and Wonogiri Regencies. Data was obtained through interviews, surveys, and observations. The study results indicate that service quality is the main factor contributing to farmer satisfaction, placing it in the first rank with a very high level of satisfaction. Positive testimonials from other farmers also show a significant level of satisfaction, ranking second. The experience of using the FC, which ranks third, also positively impacts the satisfaction level of farmers. Meanwhile, the accessibility of FCs and the quality of their products received quite satisfactory ratings in the fourth and fifth ranks. The financial institution's marketing strategy is ranked sixth with the same assessment, indicating the potential for improvement. This finding has implications for expanding responsive and more responsive services for farmer satisfaction using FCs. Recommendations for future research involve further exploring the factors that influence satisfaction levels and the development of more effective strategies in the promotion and marketing of FCs.